On Hardy spaces of local and nonlocal operators - Bogdan, Krzysztof; Dyda, Bartłomiej; Luks, Tomasz (Hiroshima Mathematical Journal)

Application of Event Based Decision Tree and Ensemble of Data Driven Methods for Maintenance Action Recommendation - Kimotho, James Kuria; Sondermann-Wölke, Chritoph; Meyer, Tobias; Sextro, Walter (International Journal of Prognostics and Health Management)
This study presents the methods employed by a team from the department of Mechatronics and Dynamics at the University of Paderborn, Germany for the 2013 PHM data challenge. The focus of the challenge was on maintenance action recommendation for an industrial machinery based on remote monitoring and diagnosis. Since an ensemble of data driven methods has been considered as the state of the art approach in diagnosis and prognosis, the first approach was to evaluate the performance of an ensemble of data driven methods using the parametric data as input and problems (recommended maintenance action) as the output. Due to close correlation of parametric data of different problems, this approach produced high misclassification rate. Event-based decision trees were then constructed to identify problems associated with particular events. To distinguish between problems associated with events that appeared in multiple problems, support vector machine (SVM) with parameters optimally tuned using particle swarm optimization (PSO) was employed. Parametric data was used as the input to the SVM algorithm and majority voting was employed to determine the final decision for cases with multiple events. A total of 165 SVM models were constructed. This approach improved the overall score from 21 to 48. The method was further enhanced by employing an ensemble of three data driven methods, that is, SVM, random forests (RF) and bagged trees (BT), to build the event based models. With this approach, a score of 51 was obtained . The results demonstrate that the proposed event based method can be effective in maintenance action recommendation based on events codes and parametric data acquired remotely from an industrial equipment.
Keywords: maintenance decision; Bagged trees; Decision trees; PSO-SVM; Random forests

Gender, Diversity and a Competence Based Computer Science Curriculum - Weber, Jutta; Crutzen, Cecile (Festschrift for Christina Mörtberg)

Changes of users' discursive behavior in HRI - Lohse, Manja; Rohlfing, Katharina; Wrede, Britta (Presentation at the 10th International Pragmatics Conference (IPrA))
Whether interacting with a colleague from another department, a child with distinct cognitive and linguistic skills or a foreigner with different cultural background, humans try to adapt to their communication partners. The adaptation allows for a flow in communication and thereby for successful turn-taking. In contrast, when users communicate with artificial systems often reduced flow and turn-overtaking 4 are observable. The reasons for these insufficiencies may lie in the fact that little is known about the turn-taking strategies that dialogue systems should pursue 4. In our approach, we postulate that it is the feedback of the system and the interpretation of the feedback by the user that are in the center of an adaptation process As a result, one way to improve HRI, and especially its communicational flow, is to focus on different types of feedback and how they affect the user{’} discursive behavior. In contrast to former work concentrating on telephone based speech systems or multimodal systems consisting of a touch screen and speech 1, 2, 5, we study an embodied interaction with the service robot BIRON (BIelefeld RObot CompanioN). The general goal of the studies is to develop a situated system that can learn the spatial environment as well as the names and visual appearance of objects. Therefore, BIRON can not only understand spoken speech but also co-verbal deictic references to objects in the scene and carry out mixed-initiative dialogues. In our study, the subjects were asked to introduce objects to the robot by showing and pointing. This very restricted goal allowed us to compare verbal and gestural behavior across subjects. We analyzed the interactions of 15 native German speaking users communicating with BIRON. The interaction was carried out with the fully autonomous mode of BIRON, except for the speech recognition, which was simulated by keyboard input in order to avoid speech recognition errors. By using the autonomous interaction system, we were able to produce realistic communication sequences including problems caused by the complex interaction of the diverse perceptual system components. In analyzing the users{’} discursive behavior, we noticed different task-related interaction strategies. Focusing on subject{’}s consistency and changes of strategies in the course of the ongoing turn-taking, we analyzed which feedback of the system caused a change of a strategy within a user. We found that subjects decided for one strategy addressing one perceptual channel (vision or speech) of the system and used it as long as they did not receive any feedback about the failure of this specific channel. We observed a change in strategy when it became obvious to the subject via feedback that a particular perceptual channel was not working appropriately. The change in strategy was likely to maintain the interaction flow and thereby the user satisfaction. While these results support previous findings indicating when and how users change strategies 1, 5, they give new insights into the discursive behavior, i.e. into the repertoire of strategies in embodied and situated interaction. The results imply that within turn-taking, users interpret the system{’}s feedback and thus verify their model of the capabilities of the interlocutor. Thus, the change in discursive strategy is an indicator of users{’} expectation of how the robot functions 3. In further studies we plan to deliberately vary the robots misunderstandings and integrate the personality traits of the subjects into the research on strategies.

Unscharfe Produktionsprogrammplanung bei Alternativproduktion - Betz, Stefan

A honeypot for the exploration of spammers' behaviour - Schryen, Guido (IATAC IAnewsletter)

How Security Problems Can Compromise Remote Internet Voting Systems - Schryen, Guido (Workshop of the ESF TED Programme)
Remote Internet voting systems still suffer from many security problems which rely on the clients, the servers, and the network connections. Denial-ofservice attacks and viruses still belong to the most challenging security issues. Projects and studies like the ?Voting Technology Project? of CALTECH and MIT or SERVE of the US Department of Defense set up to gain experience evidence many of the notional weaknesses of current Internet voting systems.

Towards a Generic Model for AOP (GEMA) - Mehner, Katharina; Rashid, Awais

Extended Model Relations with Graphical Consistency Conditions - Hendrik Hausmann, Jan; Heckel, Reiko; Sauer, Stefan (Proceeding of the Workshop on Consistency Problems in UML-based Software Development (satellite event of the UML 2002), Dresden (Germany))
Consistency of models and model transformations are strongly interrelated topics. It is thus desirable to have a single notation to express model properties concerning both aspects. When using meta modeling techniques, graph transformations are a natural candidate to express model transformations. This paper explores the use of graph transformations for denoting consistency conditions between models. This technique yields benefits for different types of interrelation between transformation and consistency. A special focus is put on the generation of automatic consistency-establishing transformations.

On the Specification and Analysis of Protocols in UML-RT - Engels, Gregor; Küster, Jochen; Groenewegen, Luuk